The Relationship Between Phubbing Behavior and Student Empathy at Garudaya Bontonompo Vocational School - Muhrawati, Muhrawati; Alamsyah, Alamsyah; Putri, Rukiana Novianti (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
This study investigates the relationship between phubbing behavior and students’ empathy in the context of digital learning at SMKS Garudaya Bontonompo, Indonesia. The research employs a quantitative correlational design with a sample of 135 students selected through simple random sampling. Data were collected using two standardized instruments: the Phubbing Behavior Scale and the Empathy Scale, both of which demonstrated high reliability coefficients. Descriptive and inferential statistical analyses were conducted using SPSS version 23.0. The results indicate a strong and significant negative correlation (r = –0.806, p < 0.05) between phubbing behavior and empathy, suggesting that increased smartphone-centered activity corresponds with decreased emotional understanding. These findings emphasize the need for balanced digital engagement in educational settings and highlight the psychological impact of smartphone dependency on social-emotional development. The study recommends integrating social-emotional learning (SEL) and digital citizenship education into classroom practices to foster empathy and responsible technology use among students.